Quality assessment and antioxidant study of Pleurotus djamor (Rumph. ex Fr.) Boedijn - Krishnendu Acharya, Somanjana Khatua, Saswata Ray (Journal of Applied Pharmaceutical Science, 2017)
Pleurotus djamor is an important oyster mushroom that has attracted much attention due to its high nutritional value and diverse therapeutic properties. However, quality standards of this species remain unexplored so far. For this purpose, microscopic features of powder such as physical characters, spore measurement, type of hyphae were examined and described. Physico-chemical parameters like organoleptic features and fluorescent behaviour against 16 reagents were also determined. In addition, an alcoholic extract was prepared using methanol as solvent to characterize the mushroom chemically and biologically. Preliminary mycochemical analysis indicated presence of major bioactive components in the following order of phenol> ascorbic acid> flavonoid> β-carotene> lycopene. To determine phenolic fingerprint of the extract, an HPLC profile was recorded. The chromatogram indicated existence of at least nine phenolic components in the extract. Moreover, antioxidant activity of the macrofungus was also evaluated using in vitro assays like DPPH radical scavenging activity (EC50 value 0.653 mg/ml) and total antioxidant capacity (16.67 µg AAE/mg of extract). In summary, the data as described in this study are significant towards future identification and authentication of genuine mushroom material establishing the pharmacognostic standards. Furthermore, results of antioxidant study indicate that the mature fruiting bodies could be valuable for defending radical induced ailments.
Keywords: Antioxidant property, HPLC, Medicinal mushroom, Pharmacognostic standardization, Physico-chemical evaluation.